RIG-I Has a Role in Immunity Against Haemonchus contortus, a Gastrointestinal Parasite in Ovis aries: A Novel Report - Banerjee, Samiddha; Pal, Aruna; Pal, Abantika; Mandal, Subhas Chandra; Chatterjee, Paresh Nath; Chatterjee, Jayanta Kumar (Frontiers in Immunology, 2021)
RIG-I belongs to the DExD/H box RNA Helicases. It is a Pattern Recognition Receptor (PRR), playing a crucial role in the immune system and is a germ line encoded host sensor to detect Pathogen Associated Molecular Patterns or PAMPs. So far reports were available for the role of RIG-I in antiviral immunity. This is the first report we have documented the role of RIG-I in parasitic immunity. Haemonchus contortus is a deadly parasite affecting sheep industry which has a tremendous economic importance and the parasite reported to be prevalent in the hot and humid agroclimatic region. We had characterized RIG-I gene in sheep (Ovis aries) and identified the important domains or binding site with Haemonchus contortus through in silico studies. Differential mRNA expression analysis revealed upregulation of RIG-I gene in abomassum of infected sheep compared to that of healthy sheep, further confirming the findings. Thus it is evident that in infected sheep, expression of RIG-I is triggered for binding to more pathogen (Haemonchus contortus). Genetic similar studies with human and other livestock species to reveal that sheep may be efficiently used a model organism for studying the role of RIG-I in antiparasitic immunity of human.